An overview of the health and management challenges of rural poultry stock in North Central Nigeria - Aiyedun, Julius Olaniyi; Oludairo, Oladapo Oyedeji (Journal of Advanced Veterinary and Animal Research, 2016)
Objectives: Poultry production in rural areas is considered as an important source of livelihood for most rural communities. The objective of the present study was to investigate the major factors affecting production of rural poultry in three senatorial districts in North Central Nigeria namely Kwara Central, Kwara South and Kwara North. Materials and Methods: The major factors affecting production of rural poultry were investigated using structured questionnaire to gather data on health and management practices between January to December 2014. Results: The socio-economic characteristics of respondents showed that majority of rural poultry farmers are women and illiterate, that sourced fund from their personal savings, relations and friends. The study also showed that seasonal variation and disease significantly influenced poultry production and its marketability. Conclusion: There is the need to put in place enabling environment to encourage commercialization of rural poultry production in Nigeria and globally. http://dx.doi.org/10.5455/javar.2016.c127